PENYELESAIAN WANPRESTASI PERJANJIAN ANTARA PEMILIK BISNIS DENGAN SELEBGRAM DALAM MEMPROMOSIKAN SUATU PRODUK SECARA ONLINE - Umul Khair; Ana Ramadhona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The development of the internet in Indonesia has changed very quickly over time. The large number of online shop accounts that have emerged then makes business and business competition even higher. One way that is widely used by online shop business owners today to get consumers' attention is to use the services of an artist on Instagram, or what is commonly called a